The Influence of Social Media Instagram Promotion and Hedonic Shopping Motives on Purchase Decision at Shopee Clarandkei with Trust as a Moderating Variable - Lintang, Shinta Ayu; Padmalia, Metta (Sekolah Tinggi Manajemen IPMI, 2023)
This study aimed to examine the effect of social media Instagram promotion on purchase decisions, hedonic shopping motives on purchase decisions, trust in moderating the effect of social media Instagram promotion on purchase decisions, and trust in moderating the effect of hedonic shopping motives on the purchase decision. The independent variables comprised Instagram promotion (x1) and hedonic purchasing motives (x2); on the other hand, purchase decision served as the dependent variable (y), and trust served as the moderating variable (m). This quantitative research used the Partial Least Square - Structural Equation Modeling (PLS-SEM) analysis method. The data was processed using SmartPLS 4 software. The sampling utilised a purposive sampling method and the instrument questionnaire using a Likert scale. Using Google Form media, the questionnaire was disseminated online. The study’s population consisted of 3.800 Instagram followers of Clarandkei. This study’s sample consisted of 180 respondents who enjoyed online clothing purchasing and had purchased clothing from Shopee Clarandkei at least once. The study’s findings indicated that social media Instagram promotion and hedonic shopping motives significantly and positively affected purchase decisions; trust moderates the effect of social media Instagram promotion on purchase decisions significantly and positively; however, the trust did not moderate the effect of hedonic shopping motives on the purchase decision.